Comprehensive review of angioid streaks - Sindhuja Kandasamy; Nawazish Shaikh; Abhidnya Surve; Somya Kumari; Amber A. Bhayana; Pradeep Kumar; Rohan Chawla; Vinod Kumar (Indian Journal of Ophthalmology)
Angioid streaks are irregular breaks in the brittle Bruch’s membrane and commonly present as pigmented linear lines radiating from the optic disc. They may be associated with systemic disease in up to 50% of the patients. Systemic diseases such as pseudoxanthoma elasticum, Paget’s disease, and hemoglobinopathies are commonly associated with angioid streaks. However, they may be idiopathic in a small number of cases. Patients may be asymptomatic until complications such as choroidal neovascular membrane and subretinal hemorrhage involving the fovea develop. Due to the brittle nature of Bruch’s membrane, even minor trauma could lead to subretinal hemorrhage in these eyes. Diagnosis is commonly made through clinical examination and investigations such as fundus autofluorescence and optical coherence tomography. Treatment consists of management of the choroidal neovascular membrane commonly through intravitreal antivascular endothelial growth factor injections. In this review, we provide an overview of angioid streaks right from their epidemiology to their management.